Research hotspots and trends of non-invasive vagus nerve stimulation: a bibliometric analysis from 2004 to 2023 - Chen, Mingyue; Yang, Chunlan; Chen, Yin; Nie, Kailu; Wang, Tingting; Qu, Yun (Frontiers in Neurology, 2024)
Objectives Non-invasive vagus nerve stimulation (nVNS) is an emerging neuromodulation technique in recent years, which plays a role in nervous system diseases, psychiatric diseases, and autoimmune diseases. However, there is currently no comprehensive analysis of all the literature published in this field. Therefore, in this article, a bibliometric analysis will be conducted on all the literature published in the field of nVNS in the past 20 years. Methods All articles and reviews published in this field from 2004 to 2023 were extracted from the WOS core database. VOSviewer 1.6.18.0, Scimago Graphica, CiteSpace 6.2.R2, and Excel 2021 were used to analyze the number of publications, participating countries, institutions, authors, references, and research hotspots in this field. Results A total of 843 articles were included in the bibliometric analysis of nVNS. Over the past 20 years, the number of publications in this field has gradually increased, reaching a peak in 2023. The United States and China ranked top two in terms of publication volume, and institutions from these two countries also ranked high in terms of publication volume, citation count, and collaboration intensity. Rong Peijing is the author with the most publications, while Bashar W Badran is the most cited author. Articles in the field of nVNS were most frequently published in Frontiers in Neuroscience, while Brain Stimulation had the most citations. Currently, research hotspots in nVNS mainly focus on its application in diseases and related mechanisms. Conclusion We conducted a comprehensive analysis of the field of nVNS, clarifying the previous research directions, which is helpful to expand its indications and promote clinical application.